2016
DOI: 10.1093/ndt/gfv440
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal inflammation precedes encapsulating peritoneal sclerosis: results from the GLOBAL Fluid Study

Abstract: The peritoneal cavity has higher levels of inflammatory cytokines during PD in patients who subsequently develop EPS, but neither inflammatory cytokines nor peritoneal solute transport clearly discriminates EPS cases. Increased systemic inflammation is also evident and is probably driven by increased peritoneal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 26 publications
1
33
2
2
Order By: Relevance
“…Previous studies have suggested that a number of proteins, primarily inflammatory biomarkers (IL-6, TNF-α, MCP-1, CCL-15, PAI-1), were slightly increased in the PDE of patients who subsequently developed EPS (10,49,(64)(65) , but were not identified by our proteomics approach. Previous studies used a targeted ELISA based approach, which h a s h i g h s e n s i t i v i t y a n d s u b s e q u e n t l y resolution.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous studies have suggested that a number of proteins, primarily inflammatory biomarkers (IL-6, TNF-α, MCP-1, CCL-15, PAI-1), were slightly increased in the PDE of patients who subsequently developed EPS (10,49,(64)(65) , but were not identified by our proteomics approach. Previous studies used a targeted ELISA based approach, which h a s h i g h s e n s i t i v i t y a n d s u b s e q u e n t l y resolution.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, lower levels of 1-PI and apo A-IV may indicate an active inflammatory process which might contribute to EPS development (49) . The latter is further supported by the observed increases in Complement factor expression (43) .…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Furthermore, recent data from the GLOBAL Study showed that patients who developed encapsulating peritoneal sclerosis had earlier higher dialysate levels of IL-6 during PD. 53 These two scenarios would fit well into the concept that, depending on a pathophysiologic context, IL-6 can either be crucial for host defense or promote chronic disease. 28 Here, we show that dialysate IL-6 and sIL-6R can act together through the trans-signaling pathway controlled by the STAT3-SP4 axis to upregulate mesothelial VEGF production during peritonitis.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, our transcriptome data relate the functional results obtained with the streamlined assay to molecular mechanisms underlying enhanced response to TLR-stimulation. Unlike elevated basal levels of peritoneal IL-6 in PD patients, which predispose to membrane transformation 37, 38 , increased response to bacterial stimuli would more likely reduce peritonitis rates. However, further large scale trials are required to elucidate whether findings obtained in the settings of sepsis and other disorders can be translated to PD.…”
Section: Discussionmentioning
confidence: 99%